Unlocking Efficiency: Seaport Infrastructure, Warehouse Integration, and Commodity Availability - Atong Soekirman (Dinasti International Journal of Education Management And Social Science, 2024)
This study investigates the interaction and impact of key variables in the supply chain, including commodity availability, shipping information, port infrastructure, warehouse integrators, and fuel prices in reverse logistics. Through a deeper understanding of these variables, this study aims to help companies identify challenges, optimize operational performance, and develop adaptive strategies in the face of market and environmental changes. Conduct a thorough literature review of related research in the areas of port infrastructure, warehouse integration, and commodity availability to gain a deep understanding of current issues and trends. This qualitative research contributes to the results of its research for reference and is used by other researchers. By paying attention to all these factors, companies can improve the efficiency and effectiveness of their reverse logistics operations and reduce their activities' environmental impact. In addition, further research and proper strategy implementation are essential to achieve optimal results in reverse logistics.